2010
DOI: 10.1186/cc9334
|View full text |Cite
|
Sign up to set email alerts
|

Post-hypothermic cardiac left ventricular systolic dysfunction after rewarming in an intact pig model

Abstract: IntroductionWe developed a minimally invasive, closed chest pig model with the main aim to describe hemodynamic function during surface cooling, steady state severe hypothermia (one hour at 25°C) and surface rewarming.MethodsTwelve anesthetized juvenile pigs were acutely catheterized for measurement of left ventricular (LV) pressure-volume loops (conductance catheter), cardiac output (Swan-Ganz), and for vena cava inferior occlusion. Eight animals were surface cooled to 25°C, while four animals were kept as no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
33
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 53 publications
10
33
3
1
Order By: Relevance
“…These results in isolated cardiomyocytes are consistent with the contractile dysfunction induced by H/R in rat papillary muscle (14), and the left ventricular dysfunction induced by H/R in rat heart (10,16,38,40). These results are also consistent with the clinical observation of ventricular dysfunction during rewarming shock following accidental hypothermia (21).…”
Section: Discussionsupporting
confidence: 93%
“…These results in isolated cardiomyocytes are consistent with the contractile dysfunction induced by H/R in rat papillary muscle (14), and the left ventricular dysfunction induced by H/R in rat heart (10,16,38,40). These results are also consistent with the clinical observation of ventricular dysfunction during rewarming shock following accidental hypothermia (21).…”
Section: Discussionsupporting
confidence: 93%
“…Experimental models of deep hypothermia and rewarming confirm and explain these clinical findings [15,16]. In an experimental animal model of DHCA, left ventricle contractility, relaxation and afterload were markedly, but transiently, depressed early after reperfusion and mildly depressed late after reperfusion [17].…”
Section: Discussionmentioning
confidence: 94%
“…During cooling, studies on isolated papillary muscle show a positive inotropic effect of hypothermia per se [70]. In the intact pig however, cooling induce a reduction of cardiac contractile function and SV [33]. Lewis and colleagues showed that the inotropic effect of increasing heart rate during normothermic conditions in man, is lost at a core temperature of 33 °C [71], independent of pharmacologic interventions.…”
Section: Resultsmentioning
confidence: 99%
“…Increased levels of cAMP will increase such PKA-mediated Ser 23/24 phosphorylation and give a negative inotropic effect. Such phosphorylation will also enhance cardiac relaxation [32], which is normalized during rewarming from hypothermia as diastolic function is restored [33]. Thus, favorable or harmful effects of β 1 -agonists administration in hypothermic subjects appears associated to inotropic rather than lusitropic properties, as hypothermia-induced cardiac dysfunction is an isolated impairment of systolic function [1].…”
Section: Methodsmentioning
confidence: 99%